Religion in the Media Age - Stewart M. Hoover (Routledge, 2006)
Religion and the media seem to be ever more connected as we move further into the twenty-first century. It is through the media that much of contemporary religion and spirituality is known. Notable events and icons seem to emerge with increasing frequency. In recent years alone weâ€™ve seen the mediated events of the September 11, 2001 and July 7, 2005 terror attacks, widely covered scandals in the US and European Catholic Churches, public struggles within religious groups over social values such as gay rights, US political campaigns dominated by mediated discourses of religion, the re-emergence of religion in European political and social life, Mel Gibsonâ€™s The Passion of the Christ and William Arntzâ€™s What the Bleep Do We Know?,1 Tom Cruise joining John Travolta as entertainment industry icons of Scientology, Madonna playing the same role in relation to Kabbalah, an increasing number of popular television and film portrayals of gothic, horror, science fiction, magical, mysterious, and conventional religion and spirituality, and controversies over the very presence of religion â€“ of various kinds â€“ in â€œthe media.â€ The realms of â€œreligionâ€ and â€œmediaâ€ can no longer be easily separated, and it is the purpose of this book to begin to chart the ways that media and religion intermingle and collide in the cultural experience of media audiences. It has been easy for us to think of relations between religion and the media in institutional terms. We have thought of religion as a set of traditions, dogmas, practices, and institutions that exist in an autonomous position vis-Ã -vis â€œthe culture.â€ We have thought of culture as merely making communication, interaction, memory, and history possible within social relations by providing the languages and contexts of interaction. In this â€œreceivedâ€ view, society is the more fixed and hard set of categories within which human beings must learn to function. It provides the structures and boundaries within which things like â€œcultureâ€ and â€œreligionâ€ do their work. And, individual identity is somehow a result of these other factors, conditioned â€“ even mostly determined â€“ by them.